Model Pembelajaran Reading Questioning and Answering Berpengaruh Terhadap Hasil Belajar Biologi Siswa di Madrasah Aliyah - Sari Ramadani; Alfian; Nanda Gusriani (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sulthan Thaha Saifuddin Jambi, 2023)
The purpose of this research is to find out the effect of the Reading Questioning and Answering (RQA) Learning Model on Student Biology Learning outcomes at Madrasah Aliyah As’ad Olak Kemang Jambi City. This research is a quantitative study using the Postest-Only Control Design while data collection is done with final test (Post-test). Analysis with ttest. The sampling technique used is Simple Random Sampling with a sample 30 students in the experimental class and 30 students in the control class. The research data obtained the highest score in the experimental class was 95,7 and the lowest score was 48 with an average of 76 while in the control class the highest score was 95,7 and the lowest score was 43,5 with an average of 70,20. The ttest significant level of 5% = 1,672 and 1% = 2,394 obtained 1,672 < 2,447 >2,394. So tcount > ttable or HO is rejected and Ha is accepted with a large effect of 0,6 on the criteria beingthe persentage 38,2 %. Which means there is a significant difference between student learning outcomes using the Reading Questioning and Answering (RQA) Learning Model with those not using the Reading Questioning and Answering (RQA) Learning Model outcomes at Madrasah Aliyah As’ad Olak Kemang, Jambi City. Keywords : The Reading Questioning and Answering (RQA) Learning Model, result of study.